The Intergroupe Francophone du Myélome experience with thalidomide (Hematology Meeting Reports, 2009)
The Intergroupe Francophone du Myélome (IFM) has conducted studies of thalidomide as treatment for relapsed or refractory multiple myeloma (MM) and as first-line therapy. One study comparing two doses of thalidomide (100 vs 400 mg/d) in relapsed patients has not yet been analyzed. Another study testing low-dose thalidomide in combination with melphalan and prednisone (MP) in elderly patients (>75 years) with newly diagnosed MM is ongoing. Three studies are presented here. Of these, one phase 2 study in relapsed/refractory patients has already been published; the other two have been presented in meetings only.